Cortical motor areas are activated early in a characteristic sequence during post-movement processing - Bender, Stephan; Becker, David; Oelkers-Ax, Rieke; Weisbrod, Matthias (NeuroImage, 2006)
During motor learning in goal-directed reactions, a specific movement has to be associated with feedback about the movement's success. Such feedback often follows when the movement is already over. We investigated the time-course of post-movement cortical motor processing by high-resolution analysis of lateralized post-movement potentials in forewarned and simple reaction time tasks. In both paradigms we could separate a post-movement component (motor postimperative negative variation-mPINV) peaking about 500 ms after the button press (confirmed by electromyogram and accelerometer). mPINV could not be sufficiently explained by motor cortex activity related to EMG output and/or by sensory feedback. mPINV was enhanced by long intertrial intervals and its lateralization changed with response movement side. Its scalp potential distribution resembled (pre-)motor cortex activity during preceding movement stages and differed from the frontal motor potential peak (proprioceptive and somatosensory reafferent feedback); suggesting post-movement activation of pre-/primary motor cortex. Dipole source analysis yielded a single radial source near premotor cortex which explained lateralized mPINV almost completely. mPINV was present in simple reaction time tasks, indicating that mPINV is an independent component and does not represent delayed resolution of pre-movement negativity. An equivalent of “classical” PINV (cPINV) occurred later over prefrontal and anterior temporal sites in simple and forewarned reaction time tasks. Our results suggest that high-resolution analysis of lateralized movement-related potentials allows to image post-movement motor cortex activity and might provide insights into basic mechanisms of motor learning: A characteristic sequence might involve motor cortex activation (mPINV) before “higher order associative areas” come into play (cPINV).